Sustainable treatment of tanneries wastewater using low-cost and highly efficient materials - Abdelkader, Sarah Ehab (AUC Knowledge Fountain, 2020)
Chromium sulfate salt (Cr2(SO4)3) is the tanning agent used in the chrome tanning process, but during the process around 30 or 40% of the chromium is discharged as chromium III residues in the tannery's wastewater resulting in serious health and environmental problem in case of discharging to the environment without appropriate treatment. The main objective of this study is to investigate the efficiency of using solid waste materials for low-cost trivalent chromium removal from tanneries wastewater. This study was conducted in 5 phases: phase I, phase II, phase III, phase IV and phase V. In phase I, two groups of waste materials, organic and inorganic waste materials, were tested for the removal of trivalent chromium from aqueous solution and the results indicated that the group of inorganic waste materials, including marble powder (MP) and cement bypass kiln dust (CKD), showed better removal efficiency of chromium III. In phase II, the optimum mixing conditions, best removal efficiency and the energy required in the treatment process for both MP and CKD were studied. The results indicated that CKD showed better removal efficiency and lower energy consumption. In phase III, CKD was selected to carry further investigation on the treatment performance, operating conditions and the mechanisms for the removal of trivalent chromium. In phase IV, real samples wastewater was collected from a tannery in Egypt and it was tested for chromium III removal using CKD under the mixing and operating conditions obtained in phases II and III. The results recorded removal efficiency of chromium III of 99.97%. Finally, in phase V, chromium III recovery from the precipitated sludge using sulfuric acid (H2SO4) were studied. The best chromium III recovery efficiency was found to be 96.13 % using 7.75% H2SO4 solution and sludge dose of 2.5g.